Feminisation of migration, precarious occupations, and workplace-based stokvels. A case of Zimbabwean women migrants working in the hospitality industry in South Africa - Thebe, Vusilizwe (University of Pretoria, 2024)
Thesis (PhD (Development Studies)--University of Pretoria, 2023.